Evaluation of Handling Waste System in Doulu Tourist Area, Karo Regency, Indonesia - Depari, Brian Pratama; Nasution, Zulkifli; Ginting, Nurzainah (TALENTA Publisher, Universitas Sumatera Utara, 2023)
Penatapan Doulu is one of the popular tourist areas in Karo Regency, Indonesia. Tourism activities cause waste problems that have the potential to pollute the surrounding environment. This study aims to analyze and evaluate waste problems in the Penatapan Doulu tourism area which includes waste management policies and methods, as well as providing future considerations for proposed waste management strategies through the concept of collaborative management. This study analyzes all kinds of waste generated from 30 restaurants located in the Penatapan Doulu tourist area. The method for calculating waste generation and composition is based on SNI 19-3964-1994. The results showed that the total waste generation reached 76.03 kg/day with the waste composition dominated by plastic 42.02%, fruit peels 28.07%, and food 13.46%. Evaluation of the current condition obtained a value of 2.58 which is categorized as moderate. Proposed strategies that need to be carried out in the Penatapan Doulu tourist area are making trash bins based on the type of waste and pilot village programs which are a concrete manifestation of synergy between stakeholders and handling waste problems must be carried out by all parties with collaborative management carried out effectively.Â